Roman Pollak. Portret wykładowcy uniwersyteckiego, czyli co można wyczytać z notatek studentki Zofii Muszyńskiej… i nie tylko - Gromadzka, Beata (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article characterises the didactic work of professor Roman Pollak and offers a reconstruction of the concept for teaching Polish studies which is based on his published papers on didactics, handwritten notes for seminars and lectures, texts of speeches, lectures to the Polish studies club and letters to his fellows. The image of the professor is complemented by the notes from lectures on the history of Old Polish literature taken by professor Zofia Trojanowiczowa (née Muszyńska) when she was a student of his and by the recollections of his students. The analysis of the subject material results in a portrait of a remarkable expert in literature who devoted much of his attention to thinking about university didactics and who was aware of both his own skills and his mission.